Societal factors and pregnancy outcome - Chawla, Chandra Dev (Nepal Journal of Obstetrics and Gynaecology, 2014)
DOI: http://dx.doi.org/10.3126/njog.v3i2.10822 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 1-3